THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER LOYALTY AT PT APLIKASI KARYA ANAK BANGSA (GOJEK INDONESIA) - Kurniawan, Galihtri; Sudibyo, AG (Transpublika Publisher, 2024)
In the midst of intense competition among other companies, one way to retain customers is customer relationship management (CRM). Customer loyalty which can later be used as a benchmark in the sustainability of a company that is competing fiercely with its competitors. The existence of online transportation is an innovation in the era of the times which makes technological developments develop rapidly, especially in the field of transportation. The purpose of this study is to determine whether CRM activities affect customer loyalty or not. In addition, this study will also investigate how Gojek Indonesia's CRM affects customer loyalty. This research uses quantitative methods for data collection; surveys or questionnaires are used as samples, and the sample size of respondents is 100 people. And by using bivariate data analysis by testing between 2 variables, and data processing using SPSS. According to the results of the regression test analysis, there is a significant correlation between customer relationship management and customer loyalty of PT Gojek Indonesia.